Authors versus AI: Approaches and Challenges - Vodolazka, Svitlana; Krainikova, Tetiana; Ryzhko, Olena; Sokolova, Kateryna (Aktualʹni pytanni͡a︡ masovoï komunikat͡s︡iï, 2024)
The study is aimed at typologizing the approaches to using AI by book authors, tracing the creative opportunities, legal and ethical conflicts as well as promising solutions generated by this collaboration. At the first stage of the research (July – August 2023), the theoretical sources were reviewed, and the research was conceptualized. The fundamental scientific approaches were: 1) the theory of technological determinism; 2) theory of information society; 3) diffusion of innovation theory. At the second stage (September 2023), empirical studies included: 1) monitoring of Amazon.com keywords for the availability of books created with the help of AI; 2) non-standardized expert interviews; 3) discourse analysis of Internet resources that publish both interviews and analytical, expert materials related to the problems of the book market. At the third stage (November 2023), we carried out the analysis and interpretation of the obtained results. According to the data, 1,542 AI-generated books were found at Amazon catalogues. Among them, non-fiction, created using various AI systems, prevails (65%). When creating texts, most authors use GPT modifications — ChatGPT (1021 books), ChatGPT-4 (210 books) and ChatGPT AI (197 books). The subject of this literature is wide: cooking, tourism, business, medicine, etc. There are currently five main approaches to the use of AI by authors such as: (1) AI as a technical instrument of the author; (2) AI as a partner of the author; (3) AI an imitator of the author; (4) AI as a plot sample narrator; (5) AI as an original content generator. Therefore, authors use AI at different stages of the creative process, with different intensity and for different tasks. To overcome the challenges caused by the introduction of AI in the creative industries, complex solutions are needed: new legislative norms, codes of conduct and editorial policies, improving the qualifications of authors.